Interaction between the retrotrapezoid nucleus and the parafacial respiratory group to regulate active expiration and sympathetic activity in rats - Zoccal, Daniel B. [UNESP]; Silva, Josiane N.; Barnett, William H.; Lemes, Eduardo V. [UNESP]; Falquetto, Barbara; Colombari, Eduardo [UNESP]; Molkov, Yaroslav I.; Moreira, Thiago S.; Takakura, Ana C. (Amer Physiological Soc, 2018)
The retrotrapezoid nucleus (RTN) contains chemosensitive cells that distribute CO2-dependent excitatory drive to the respiratory network. This drive facilitates the function of the respiratory central pattern generator (rCPG) and increases sympathetic activity. It is also evidenced that during hypercapnia, the late-expiratory (late-E) oscillator in the parafacial respiratory group (pFRG) is activated and determines the emergence of active expiration. However, it remains unclear the microcircuitry responsible for the distribution of the excitatory signals to the pFRG and the rCPG in conditions of high CO2. Herein, we hypothesized that excitatory inputs from chemosensitive neurons in the RTN are necessary for the activation of late-E neurons in the pFRG. Using the decerebrated in situ rat preparation, we found that lesions of neurokinin-1 receptor-expressing neurons in the RTN region with substance P-saporin conjugate suppressed the late-E activity in abdominal nerves (AbNs) and sympathetic nerves (SNs) and attenuated the increase in phrenic nerve (PN) activity induced by hypercapnia. On the other hand, kynurenic acid (100 mM) injections in the pFRG eliminated the late-E activity in AbN and thoracic SN but did not modify PN response during hypercapnia. Iontophoretic injections of retrograde tracer into the pFRG of adult rats revealed labeled phox2b-expressing neurons within the RTN. Our findings are supported by mathematical modeling of chemosensitive and late-E populations within the RTN and pFRG regions as two separate but interacting populations in a way that the activation of the pFRG late-E neurons during hypercapnia require glutamatergic inputs from the RTN neurons that intrinsically detect changes in CO2/pH.
Keywords: abdominal activity; hypercapnia; sympathetic activity; ventilation; ventral medulla